Strategic Responses of Platform Multinational Enterprises: Rethinking Competition Policy through a Comparative Institutional Perspective - Khan, Huda; Stylianou, Konstantinos; Khan, Zaheer; Wood, Geoffrey (Elsevier, 2026)
As of 2026, the battle continues between competition and regulatory policies over whether—and how much—to rein in online digital platforms. These debates have gained renewed urgency given the growing entanglement of major U.S.-based platforms with domestic political elites. The global responses of multinational platform firms (platform MNEs) further complicate this conflict. Existing research has largely focused on market dynamics and firm behavior, explaining how platforms have evaded effective oversight even as content moderation has weakened and extremist material has proliferated. Building on this literature, our paper examines cross-national variation in regulatory approaches and platform MNEs’ responses. We argue that while the Liberal/Coordinated Market Economy (LME/CME) typology provides a useful starting point for understanding regulatory diversity, contemporary regimes increasingly exhibit cross-system borrowing, institutional layering, and hybridization. Large economies in the Global South further highlight distinctive state–market relationships that challenge traditional models. Together, these differences generate novel regulatory approaches and shape distinct patterns in how platform MNEs respond to oversight efforts.
Keywords: platform MNEs; competition policy; comparative institutional perspective; digital economy; liberal market economies; coordinated market economies; fi=InnoLab|en=InnoLab|; fi=Kansainvälinen liiketoiminta|en=International Business|